Intracranial functional near-infrared spectroscopy: an animal feasibility study - Heymann, Sami; Rein, Netaniel; Zurita, Marco; Shechter, Revital; Israel, Zvi; Balberg, Michal; Medvedovsky, Mordekhay; Rosenthal, Guy (Frontiers in Medical Technology, 2025)
IntroductionFunctional Near-Infrared Spectroscopy (fNIRS) is widely used to monitor cerebral hemodynamics, however, it is limited by shallow penetration depth and susceptibility to hemodynamic noise from the scalp. A novel intracranial fNIRS (ifNIRS) system, featuring depth optrodes (optode-electrodes) and optical anchor bolts (OABs), has been proposed to address these limitations. This study investigates the feasibility of ifNIRS in a swine model under controlled interventions.MethodsThree animals were implanted with ifNIRS. Each animal with three OABs, with depth optrodes (DO) inserted into two of the OABs. Hemodynamic changes were recorded using OAB-to-OAB (OAB-OAB) and DO-to-OAB (DO-OAB) channels. Two interventions were performed to generate hemodynamic changes: rapid infusion of hypotonic saline to induce cerebral edema and blood withdrawal. Postmortem assessment for tissue damage and hemorrhage was performed. Hemoglobin concentration changes were analyzed using the Beer-Lambert equation.ResultsA decrease in total hemoglobin (tHb) levels during blood withdrawal was observed in all channel configurations that displayed relevant signals. During hypotonic saline infusion, variable patterns of tHb were observed. Postmortem findings showed minor extra-axial hemorrhages near OABs, but no intracerebral or heat-related injuries.DiscussionThis study demonstrates the feasibility of the ifNIRS system in detecting hemodynamic changes in vivo. While technical refinements are needed, ifNIRS shows promise for improving cerebral hemodynamic monitoring and enhancing diagnostic accuracy in invasive monitoring of patients with epilepsy.